Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan Video Terhadap Kemampuan Berpikir Kritis Siswa Kelas VIII Pada Materi Sistem Pernapasan di SMP Negeri 9 Halmahera Utara - Triyono Triyono; Said Hasan; Abdulrasyid Tolangara (JURNAL BIOEDUKASI, 2022)
The video guided inquiry learning model is a series of learning activities that aim to help students improve their critical thinking skills by asking questions and getting answers on the basis of student curiosity after viewing or watching the provided learning videos. This study aims to determine the effect of the video-assisted guided inquiry learning model on critical thinking skills in the material of the respiratory system for class VIII SMP Negeri 9 Halmahera Utara. This research is a Quasi Experiment. The research population was all students at SMP Negeri 9 Halmahera Utara for the 2021/2022 Academic Year with a sample of 22 students in class VIII-A and 20 students in VIII-B. Research was conducted in February 2021/2022. The instrument is a matter of critical thinking ability test. Research data were analyzed by covariance test (Anakova). The results showed that there was an effect of the video-assisted guided inquiry learning model on the critical thinking skills of Grade VIII students of SMP Negeri 9 North Halmahera with a significant level of 0.048.